2006
DOI: 10.1207/s15473333thp3401_7
|View full text |Cite
|
Sign up to set email alerts
|

How to help after national catastrophes: Findings following 9/11.

Abstract: This article found elevated levels of trauma symptoms related to the terrorist attacks of 9/11 in students at a university in Northern California. In an analogue comparison, the impact on trauma symptoms of 2 interventions-journal writing and story listening-was examined. College students were randomly assigned to write about their emotional reactions to 9/11 or to listen to stories evoking themes relevant to the national tragedy. Participants in both conditions reported significant improvements in trauma symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 43 publications
1
13
0
Order By: Relevance
“…In the last decade, college students have dealt with tragedies or disasters on national, local, and individual levels. These incidences have strong emotional and cognitive impacts on students-even those who are not directly affected (Honos-Webb, Sunwolf, Hart, & Scalise, 2006). Examples include natural disasters such as Hurricane Maria, mass shootings (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, college students have dealt with tragedies or disasters on national, local, and individual levels. These incidences have strong emotional and cognitive impacts on students-even those who are not directly affected (Honos-Webb, Sunwolf, Hart, & Scalise, 2006). Examples include natural disasters such as Hurricane Maria, mass shootings (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…This correlates with findings in the literature that a well developed sense of meaning and purpose provides a layer of protection against compassion fatigue (Friedman, 2005;Honos-Webb et al, 2006;Rasmussen, 2005;Teyber, 2006) because humanistic and transpersonal orientations place greater emphasis on existential meaning.…”
Section: Compassion Fatigue: Integrating Risk and Resiliencesupporting
confidence: 82%
“…Frankl"s time, others have built models of resilience to and recovery from psychological distress and built on an awareness of compassion, meaning and purpose (Almedom, 2005;Anadarajah & Hight, 2001;Antonovsky, 1987Antonovsky, , 1996Bryant-Davis, 2005;Friedman, 2005;Grauf-Grounds & Edwards, 2007;Harvey, 1996;Harvey & Tummala-Narra, 2007;Hernández et al, 2010;Honos-Webb, Hart, & Scalise, 2006;Linley & Joseph, 2007;Pallant & Lae, 2002;Pietrzak, Johnson, Goldstein, Malley, & Southwick, 2009;Raingruber & Kent, 2003;Sagy & Antonovsky, 2000). Linley et al (2005) life"s meaning (Almedom, 2005;Frankl, 1959Frankl, /1992Harrison & Westwood, 2009;Hernández et al, 2010;Nelson, 2010;Pietrzak et al, 2009 (Almedom, 2005;Hernández et al, 2010;Hernández et al, 2007;Ortlepp & Friedman, 2001).…”
Section: Factors Promoting Resiliencementioning
confidence: 99%
See 1 more Smart Citation
“…Based on a survey research on 511 participants following 9/11, MacGeorge, Samter, Feng, Gillihan, and Graves (2007) found that emotional support received from interaction with others had a main effect on terrorism-related depression and was associated with less depression. An experimental study by Honos-Webb, Sunwolf, Hart, and Scalise (2006) also found that both journal writing and story-listening relieved participants' trauma symptoms after 9/11.…”
Section: Asian Journal Of Communication 153mentioning
confidence: 94%